The Subject Construction and Role Mental Model Construction of Erotic Movies Based on Lacan's Desire Theory. - Feng, Shuqin (Occupational Therapy International, 2022)
Jacques Lacan is a famous French psychoanalyst, but his influence has long gone beyond the scope of psychoanalysis and has affected almost all fields of "human science." Film and psychoanalysis coincided almost simultaneously and influenced each other. But with the development of film, researchers found that film studies in the period of classic film and film semiotics have come to an end. It has certain theoretical value to explore the construction of the subject and the mental model of the erotic film based on Lacan's desire theory. Method. The body in the film and video described in this paper includes both the material body as an aesthetic object and the spiritual body with aesthetic consciousness. The so-called artistic presentation of the body element means that the beauty of the body form displayed by the actor's body in the film video is perceived by the audience, and the desire to stare is captured by the audience, thereby completing the audience's entire body composed of eyes, body, and mind. The body is not only an aesthetic object but also an aesthetic subject, and the human cognitive system is not just a closed brain. Because the nervous system, body, and environment are constantly changing and interacting, true cognition is a unified system of all three. The main part of this paper uses Lacan's psychoanalytic theory to deeply analyze the relationship between the characters shown in the film. From the cognitive impairment of the self to the failure of communication between characters, the language of uncertainty entangled by desire is removed, and the behavior and facial expressions of the movie characters are used as the analysis basis to fully interpret the inner world of the characters. This includes love, hatred, pain, struggle, and many other contradictory emotions. In addition, this paper also analyzes the metaphor of the relationship between the characters from the perspective of semiotics and discusses the description of the relationship between the characters from the lens language from the perspective of cinematography. The special meaning conveyed by the recurring elements in the film is emphasized, and the correlation between the pictures is explained from the less mentioned photographic aspect of the film. Results/Discussion. Looking at Lacan's theory, the subject, the other, and desire are linked by the subject spirit, which is the core of the connection between the three, and only through the resistance and struggle of the subject spirit can the illusion of the subject be broken. Bewilderment and the suppression of the other and desire finally become the self. And the embodiment of this true self is particularly prominent in film art. Lacan's purpose is not merely to dissolve the subject but to seek a stand in the midst of destruction, pursuing the ultimate transcendence of man's desire for the external other and internal desire.